2021
DOI: 10.1088/1742-6596/1840/1/012062
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of adaptive learning at higher education institutions by means of Moodle LMS

Abstract: E-learning courses have become popular means of delivering knowledge to students in higher education institutions. Most participants of learning process note that they benefit from the possibility to gain knowledge regardless of time, location and device they use. Among other advantages possibility to return to learnt material several times, divide material into parts, consume information through different types of educational materials (video, infographics, presentations, text, quizzes etc.) are mentioned. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 12 publications
1
47
0
10
Order By: Relevance
“…However, with further explanation, WhatsApp is a social media application that is used to socialize between individuals and groups (M. Mirzon Daheri et al, 2020;Trisnani, 2017). Teachers who experienced problems related to the use of technology and applications in carrying out online learning were caused by the lack of teacher skills in using facilities and infrastructure in online learning (Hong et al, 2021;Kim & Gurvitch, 2020;Morze et al, 2021). However, teacher skills in using technology are still lacking, especially senior teachers who are still not proficient in using devices or facilities to support the implementation of online learning (Dewi, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, with further explanation, WhatsApp is a social media application that is used to socialize between individuals and groups (M. Mirzon Daheri et al, 2020;Trisnani, 2017). Teachers who experienced problems related to the use of technology and applications in carrying out online learning were caused by the lack of teacher skills in using facilities and infrastructure in online learning (Hong et al, 2021;Kim & Gurvitch, 2020;Morze et al, 2021). However, teacher skills in using technology are still lacking, especially senior teachers who are still not proficient in using devices or facilities to support the implementation of online learning (Dewi, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the focus of these studies includes the necessity of linking the learners' needs with the features of the applications [20]. It seems important to have powerful tools to examine the effectiveness of educational applications so that they are suitable for the students [21].The studies concluded that there is a need to restructure educational applications to be adapted to the characteristics and cognitive styles of the students [22,23]. Despite the plethora of the studies that examined the effectiveness of adaptation according to the students' cognitive style on learning, these studies did not address adaptation according to CSSC and they did not explore their impact on the students' DWB [24][25][26][27] According to van de Pol, et al [28] Some researchers view scaffolding as a metaphor describing a special method of teaching that takes place in an educational setting which involves sharing tasks between the teacher and the learner.…”
Section: Adaptive Mobile Scaffold System (Amss)mentioning
confidence: 99%
“…Moodle has been implemented in universities and its use has experienced a significant increase in the era of the covid-19 pandemic (Morze et al, 2021;Polhun et al, 2021;Sugihartini et al, 2021;Zabolotniaia et al, 2020). Even before the lockdown period, it gives a great level of technological satisfaction for students (Garcia-Murillo et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%